Pengaruh Etos Kerja Islami Dan Komitmen Organisasi Terhadap Kinerja Karyawan Bank Tabungan Negara Syariah (BTN) KC Malang - Citra, Derry Pratama; Purwadi, Agus; Hakim, Imamul (Universitas Muhammadiyah Malang, 2018)
This study aims to determine the influence of Islamic work ethic and organizational commitment to the performance of employees of the BTN Syariah Malang Branch in 2018. This study uses a quantitative approach with multiple linear regression analysis method. The results of this study indicate that based on multiple linear regression analysis test results (t test) note that Islamic work ethic has a significant effect on employee performance. Likewise with organizational commitment that gives a significant effect on employee performance. Multiple linear regression analysis simultaneously (f test) known that the two independent variables of Islamic work ethic and organizational commitment have a significant effect on employee performance. The results of this study concluded that Islamic work ethic and organizational commitment has a significant effect on employee performance.